2022
DOI: 10.3390/su14031106
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Path of the Green Consumer: Surveying the Decision-Making Process from Self-Transcendent Values to Supportive CSR Intentions

Abstract: This paper examines the relationship between individual traits and values of consumers and their decision-making process pertaining to purchasing green products from companies with a strong commitment to corporate social responsibility (CSR). Guided by the theory of planned behavior (TPB), the main goal of this online survey (N = 463) is to understand the relationship between self-transcendent values, environmentalism, attitudes, norms, perceived behavioral control, intentions, and purchase frequency to better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 92 publications
2
8
0
Order By: Relevance
“…This would allow for effective audience segmentation and thus the effectual strategic communication of their ECSR programs, which will yield positive results for corporations. This is also supported by literature, as Eng et al [63] suggested, " . .…”
Section: Theoretical and Practical Implicationssupporting
confidence: 81%
See 1 more Smart Citation
“…This would allow for effective audience segmentation and thus the effectual strategic communication of their ECSR programs, which will yield positive results for corporations. This is also supported by literature, as Eng et al [63] suggested, " . .…”
Section: Theoretical and Practical Implicationssupporting
confidence: 81%
“…the more individuals feel connected to, and are concerned about, the environment, the more likely they are to hold positive attitudes towards the effectiveness of their purchasing decisions in helping to combat the climate crisis" (p. 10). Furthermore, individuals with higher motivations to mitigate the effects of the climate crisis are likely to have higher intentions to support corporations with a strong commitment to protecting the environment, and "individuals who possess high levels of supportive intentions are more likely to follow through with actual purchasing behaviors" [63] (p. 11).…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…These activities strengthen society's social status and encourage environmental conservation. New research links CSR to community performance in terms of societal and environmental efficiency [14,54,89,90]. Corporate philanthropy and donations increase a company's effectiveness and reputation.…”
Section: Csr To Community and Financial Performancementioning
confidence: 99%
“…Corporate sustainability performance has been shown to be positively related to overall financial performance (Xiao et al ., 2018). Furthermore, research shows that customers with higher levels of environmental concern are more driven to purchase environmentally friendly products (Eng et al ., 2022; Pagiaslis and Krontalis, 2014; Paul et al ., 2016) and are more willing to pay a premium price for them (Magnier et al ., 2019; Nishitani and Itoh, 2016; Stolz and Bautista, 2015). Moreover, engagement in environmentally responsible behavior has been conceptualized as an important component of corporate reputation, with scholars finding that a more positive reputation predicts greater positive word-of-mouth intentions, which in turn may influence purchasing behavior (You and Hoon, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%